(untitled) (Scientific journal of the Fergana State University, 2024)
The article says that 44 species of spiders were found in the arachnofauna of the Fergana Valley, and their species in natural ecosystems and agroecosystems are quite different from each other. In addition, the article provides information about the life cycle and biology of species belonging to the family Thomisidae, widespread in the arachnofauna of the valley. The morphology, bioecology and reproduction of spider species Ozyptilaatomaria and Thomisus onustus belonging to this family, especially common in the Fergana Valley, are discussed. In addition, photographs of the reproduction dynamics of these two species throughout the year are presented.